A Novel Space-Time-Speed Method for Increasing the Passing Capacity with Safety Guaranteed of Railway Station - Junfeng Wang; Yang Yu; Renwei Kang; Jungang Wang (Journal of Advanced Transportation)
A method for improving the passing capacity of a station without adding any track and equipment is proposed in this paper. In the process of handling train routes, by transforming the existing fixed train-approaching locking section into a variable mode, the route locking time is shortened and in-station resource consumption is reduced. This approach improves the capacity of the station. At the same time, delay of the train can be quickly returned to normal. A method of variable train-approaching locking section is discussed; a mathematical model for increasing station passing capacity is shown. Comparison between the impact of a variable train-approaching locking section and a fixed mode on the station passing capacity is shown.